(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Despite the wealth of evidence demonstrating benefits of physical activity (PA), people with arthritis commonly do not meet recommended PA levels. In Ireland, there are exercise classes available to support people with arthritis to become active, such as the “Be Active with Arthritis” physiotherapy-led programme. Evidence suggests that many attendees of such classes reduce PA levels after programme completion. PA maintenance is critical to sustain benefits and protect long-term health. This study aimed to explore barriers and facilitators to PA maintenance in those living with arthritis after completion of a physiotherapy-led exercise programme. Methods: Three focus groups were conducted with people who had completed “Be Active with Arthritis” (n = 11, 100% female). Data were analysed using the Framework Approach. Statements related to factors enabling/inhibiting PA maintenance were mapped to the Theoretical Domains Framework (TDF). Results: Facilitators were identified across 14 TDF domains (100%), and barriers were identified in 11/14 domains (79%). Salient facilitators included: 1. Environmental context and resources: Participants described having local, affordable resources/opportunities suitable for people with arthritis as an enabler. 2. Beliefs about consequences: Participants felt PA maintenance is important for their physical/mental health, as well as arthritis management. 3. Social influences: Having peers or professionals encourage and support activity was an acknowledged facilitator. Relevant barriers included: 1. Beliefs about capabilities: Participants described low confidence in their abilities due to fear of injury/causing a flare in their condition. 2. Environmental context and resources: Participants noted that cold, wet weather and rural living act as a barrier to staying active. 3. Emotion: The burden and frustration of living with a long-term condition and feeling ‘out-of-place’ in exercise facilities for the general public were seen as barriers to PA maintenance. Conclusion: This study identifies the complexity of factors enabling and inhibiting PA maintenance for those living with arthritis. There are clear gaps to be addressed in future interventions and service delivery such as managing the emotional consequences of living with a long-term condition and identifying suitable local resources for people with arthritis to continue being active. Support/Funding Source: Health Research Board/Arthritis Ireland (HRCI-HRB Joint Funding Scheme, HRCI-HRB-2022-010).